Applying the RE-AIM framework to a food literacy program evaluation - Begley, Andrea (Wiley-Blackwell, 2018)
Comprehensive evaluation of public health nutrition program aspects such as implementation fidelity needs to be conducted to understand factors that influence program success. Foodbank Western Australia’s Food Sensations for Adults wasextensively revisedin2015 to align withthe WA Department of Health’s best practice criteria for programs. The program consists of four core modules (including cooking) and one to two optional modules which enable food literacy to be contextualised to the target group. The primary target group are West Australian adults from low to middle income households with low food literacy who want to increase their food literacy skills. The evaluation has been designed using mixed methods with a multi-group repeated measures design targeting participants, educators and organisations. An informative research and evaluation plan was required for this government funded program to provide regular updates on progress over the funding period 2016-2018. The RE-AIM framework was selected as it evaluates multiple dimensions of the performance of aprogram including Reach, Effectiveness, Adoption, Implementation and Maintenance. The framework assists in guiding reporting indicators. For example, Reach is being measured by representativeness of the target population and reported sharing of program materials with family and friends. Between the start of the evaluation April 2016 until the end of June 2017, 73% of participants are from low to middle SEIFA areas (n = 834) and 73% are sharing program materials with an additional 19% intending to share (n = 657). This type of evaluation framework offers dietitians a planned way to measure a range of useful program indicators. Funding source: WA Department of Health Contact author: Andrea Begley – a.begley@curtin.edu.au